Comparative Study of the Mechanical Properties of (FS) and MIG Welded Joint in (AA7020-T6) Aluminum Alloy - Tolephih, Moneer Hammed; Mashloosh, Kadhim M.; Waheed, Zainab (Al-Khwarizmi Engineering Journal, 2011)
A comprehensive practical study of typical mechanical properties of welded Aluminum alloy AA7020-T6 (Al-Mg-Zn), adopting friction stir welding (FSW) technique and conventional metal inert gas (MIG) technique, is well achieved in this work for real comparison purposes. The essences of present output findings were concentrated upon the FSW samples in respect to that MIG ones which can be summarized in the increase of the ultimate tensile strength for FSW was 340 MPa while it was 232 MPa for MIG welding, where it was for base metal 400 MPa. The minimum microhardness value for FSW was recorded at HAZ and it was 133 HV0.05 while it was 70 HV0.05 for MIG weld at the welding metal. The FSW produce 2470 N higher than MIG welding in the bending test and a decrease in the localized grain size for FSW in the stirred zone 12 µm and it was 37 µm for MIG while it was 32 µm for the base metal.